Towards attractive texture modified foods with increased fiber content for dysphagia via 3D printing and 3D scanning - Ahlinder, Astrid; Höglund, Evelina; Öhgren, Camilla; Miljkovic, Ana; Stading, Mats (Frontiers in Food Science and Technology, 2023)
As the life expectancy worldwide increases so does age related problems such as swallowing disorders, dysphagia, which affects 10 - 30 % of people over 65 years old. For dysphagia patients the texture and rheological properties of the food, and the bolus, is critical to avoid choking and pneumonia. Texture modified foods, timbals, which are pureed ingredients reconstituted with egg and starch are often served to these patients due to their high energy density and ease of swallowing. The main concern with these foods is that they do not look visually alike the food they are replacing which can decrease the appetite and lead to frailty in the patient. To increase the visual appearance and get texturized food more reminiscent of the original food item, 3D scanning and additive manufacturing (3D printing) have been utilized to create a chicken drumstick as a proof of concept. Rheology has been used to include a dietary fiber, citrus fiber, whilst retaining the original flow profile of the textured dysphagia food. A shear thinning index of 0.4 together with a yield stress of 0.25 kPa could be used as directional values to screen rheological properties for 3D printable food. The amount of starch was reduced from 8.7 wt.% in the original formulation to 3.5 wt.% and partially replaced by 3 wt.% citrus fiber. This resulted in a retained rheological profile whilst the energy density was increased through further concentration of the formulation.